Estrategias de logística naviera para mejoramiento del desempeño laboral en el departamento comercio internacional Reybanpac 2023 - Hernández Mejía , Mónica Alexandra (2024)
In Ecuador, efficiency in shipping logistics has become a determining factor for business success. Organizations must ensure that products are transported quickly, safely and profitably through maritime routes, minimizing transit times and optimizing the loading capacity of ships. The objective of this research was to determine shipping logistics strategies to improvement of work performance in the Reybanpac 2023 International Trade Department. The methodology used the type of field, descriptive and documentary research. The methods used included the inductive – deductive and analytical – synthetic method. The population to which the interview and survey research instruments were applied was the manager of the Shipping Logistics Department of the company Reybampac C.A, and the employees who work in said department respectively. The results obtained reflect that in general the shipping logistics strategies implemented, such as the optimization of routes and delivery times, have contributed to the achievement of the established objectives, however, it is highlighted that there have been deficiencies in the continuous training of personnel, which has not allowed us to keep the team updated and prepared to face the challenges of shipping logistics. It is concluded that the aforementioned company has adopted various measures to optimize its operations. It is recommended to implement the program of continuous training and professional development workshops for the staff proposed in this research, because constant training will strengthen the knowledge and skills of the team, allowing them to face current and future challenges more effectively.